Design and application of a breathing circuit joint for preventing condensation water from gathering (一种用于防冷凝水聚集的呼吸回路接头的设计与应用) - TIAN Suai (田素爱); YANG Fangfang (杨方方); ZHANG Xinna (张新娜) (中西医结合护理)
Mechanical ventilation refers to a rescue and treatment means to improve ventilation and oxygenation through the establishment of artificial airway. Condensate accumulation is an important source of infection leading to ventilators associated pneumonia. How to safely and effectively deal with condensate in respiratory pipes is a severe challenge faced in nursing work. This paper introduces the design and application of a utility model anti-condensation water accumulation respiratory circuit joint, which effectively improves the stability of the connection between the respiratory circuit joint and the ventilator, prevents condensation water accumulation and countercurrent during use, reduces the work burden of medical staff and improves work efficiency. (机械通气是指通过建立人工气道改善通气和氧合的一种抢救和治疗手段, 冷凝水的聚集是导致呼吸机相关性肺炎的重要感染源, 如何安全有效的处理呼吸管路内的冷凝水是护理工作中所面临的严峻挑战。本研究介绍了一款实用新型防冷凝水聚集的呼吸回路接头的设计与应用, 其有效提高了呼吸回路接头和呼吸机连接的稳定性, 能有效防止机械通气过程中冷凝水的聚集和逆流, 同时减轻了医护人员的工作负担, 提高了工作效率。)